Konsep Trilogi Keilmuan Agama Islam Perspektif Asy-Syaikh Abdullah bin Husain Ba’alawiy dalam Kitab Sullam At-Taufiq - Thoha, Aziz Mukhamad (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
The trilogy of Islamic religious knowledge, namely the science of monotheism, the science of fiqh, and the science of Sufism is the main core of Islamic teachings. All three are knowledge that must be learned by every Muslim student. Which can lead a Muslim to have a pious personality physically and mentally. The concept of the scientific trilogy of Islamic religious education is contained in books written by scholars, including the book Sullam at-Taufiq by ash-Shaykh Abdullah bin Husain. This research is a library research. There are two formulations of the problem in this research; (1) What is the meaning of monotheism, fiqh, and Sufism? (2) What is the concept of the trilogy of Islamic religious in the book of Sullam at-Taufiq?. The results of this study, namely: (1) The science of monotheism is the science of Islamic faith. The science of fiqh is the science of outward sharia. While the science of Sufism is the science of the inner Shari'a. (2) The concept of the scientific trilogy of Islamic religious in the book of Sullam at-Taufiq, namely: 1) the scientific concept of monotheism, which consists of seven subjects of study of faith, 2) the scientific concept of fiqh, which consists of seven subjects of study of fiqh law, and 3) the scientific concept of Sufism, which consists of ten points of study on obedience and the immorality of the heart.